Pengaruh Likuiditas, Profitabilitas, Leverage, Ukuran Perusahaan Dan Tingkat Suku Bunga Terhadap Kondisi Financial Distress Pada 12 Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia (Periode 2012-2018) - Yoyo Sudaryo; Dyah Purnamasari; Nunung Ayu Sofiati; Ana Hadiana (Ekonam: Jurnal Ekonomi, Akuntansi & Manajemen, 2019)
ABSTRACT: Financial distress is a condition in which the company's financial condition is in an unhealthy state, but has not yet experienced bankruptcy. In Indonesia, several manufacturing companies experience financial instability, manufacturing profits tend to fluctuate, and some companies even experience negative operating income in 2010-2016. Financial distress has a great influence where not only the company will suffer losses but also the stakeholders. One way to predict financial distress is by analyzing financial ratios. This study aims to analyze the effect of liquidity, profitability, leverage, company size and interest rates on financial distress. This study uses quantitative research methods that have the characteristics associated with numerical and objective. The independent variables in this study are Liquidity (X1), Profitability (X2), Leverage (X3), Company Size (X4), and Interest Rate (X5) and the dependent variable in this study is Financial Distress (Y). The scale used is the ratio and nominal scale. The results of research and discussion show that in partial testing (t test), obtained from the tcount for Liquidity (CR) of 4.324 and the tcount for Profitability (ROA) of 2.441 is greater than the table of 1.989. And the tcount for Company Size is -4,059 smaller than the table value of -1,989. As for the variable Leverage (DAR) and Interest Rates, it has no effect on Financial Distress. The assessment is obtained from the tcount for Leverage (DAR) of -0.350 and the tcount for the Interest Rate of 1.080 is smaller than the table of 1.989. Whereas in simultaneous testing (F test) Liquidity (CR), Profitability (ROA), Leverage (DAR), Company Size and Interest Rates simultaneously affect the Financial Distress. The coefficient of determination obtained by 48.8%, while the remaining 51.2% is influenced by other factors that are ignored by the authors in this study.